A combined epicardial implantation and subsequent extraction strategy in pacemaker device infection in pacemaker‐dependent patients. Issue 8 (20th June 2018) - van den Brink, Floris S.; van Dijk, Vincent F.; Boersma, Lucas V.A.; Wijffels, Maurits C.E.F.; Gelissen, John; Daeter, Edgar; Sonker, Uday; Balt, Jippe
Abstract: Introduction: Treatment infections is challenging in pacemaker (PM) dependent patients. We proposed a novel implantation strategy for this group of patients. Methods: Patients who were PM dependent and were admitted with a PM infection received a combined procedure of left ventricular (LV) epicardial implantation of a PM lead and subsequent extraction of the infected system. No temporary pacing wire was used and the PM generator was placed in the left flank. Results: Between 2012 and 2015 we treated 16 patients who were PM dependent and with a PM infection. The majority of patients were male (81% [13/16]) and the median age was 71 years (50–91). The cause of infection was valvular endocarditis in 38% (6/16), lead infection in 25% (4/16), and isolated pocket infection in 38% (6/16). All patients underwent epicardial implantation of a LV lead (1084T bipolar lead; St. Jude Medical Myodex, St. Paul, MN, USA) and extraction of the infected device. There was no occurrence of periprocedural mortality and no postprocedural tamponades. There was one complication in the form of a hemorrhage at the infected device extraction site. In the median follow‐up period of 17 months there were four of 16 deaths, none of which were attributable to epicardial LV implantation. LV‐lead threshold was 1.1V (±0.7V) upon implantation that increased to 1.2V (±0.6V) at 0.4‐ms pulse duration. There were no reinfections of the epicardial lead or device. Conclusion: Epicardial left ventricle PM implantation and subsequent extraction of an infected PM in PM‐dependent patients is feasible and safe with good long‐term outcome.